MANAJEMEN KAS PADA LEMBAGA PENDIDIKAN - Erwin Erwin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
Cash management as a fundamental function within a company. Similarly, in an educational institution, cash management is not as important as academic administration or other administration. Operational agencies will not run smoothly if not backed up with good cash management. Cash management is needed because cash is the most liquid assets so it is easy to transferable without leaving a trace. Departing from educational institutions operating revenues primarily from student tuition which means life or death depends on the ability of educational institutions / purchasing power at that time. Therefore cash management should be set as well - it's good to anticipate the cash deficit in the current period.